Properties of a Surface-Gate-Controlled Two-Dimensional Electron Gas in Undoped GaAs/AlGaAs Heterostructures - Choi, Hyungkook; Nam, Youngwoo; Lee, Jae Hyun; Son, Seok Kyun (Journal of the Korean Physical Society, 2020)
We studied the properties of electron transport in mesoscopic GaAs/AlGaAs heterostructure without any intentional dopants in which an external electric field defined the two-dimensional electron gas (2DEG). An electrically formed 2DEG without intentional doping offers many advantages because of the absence of high concentrations of charged scattering centers. We demonstrate that the electron concentration can be easily tuned by varying the gate voltage. This tunability was observed for a high-quality 2DEG with a carrier density ranging from 0.75 to 3.34 × 1011 cm−2, for which the corresponding mobility ranged from 0.26 to 2.93 × 106 cm2V−1s−1. The mobility of the 2DEG is closely followed the experimental power law for high-mobility wafers, μ ∞ n2D0.7.
Keywords: GaAs/AlGaAs heterostructure; Two-dimensional electron gas; Undoped devices